WRN modulates translation by influencing nuclear mRNA export in HeLa cancer cells - Manuel Iglesias-Pedraz, Juan (2020)
Background The Werner syndrome protein (WRN) belongs to the RecQ family of helicases and its loss of function results in the premature aging disease Werner syndrome (WS). We previously demonstrated that an early cellular change induced by WRN depletion is a posttranscriptional decrease in the levels of enzymes involved in metabolic pathways that control macromolecular synthesis and protect from oxidative stress. This metabolic shift is tolerated by normal cells but causes mitochondria dysfunction and acute oxidative stress in rapidly growing cancer cells, thereby suppressing their proliferation. Results To identify the mechanism underlying this metabolic shift, we examined global protein synthesis and mRNA nucleocytoplasmic distribution after WRN knockdown. We determined that WRN depletion in HeLa cells attenuates global protein synthesis without affecting the level of key components of the mRNA export machinery. We further observed that WRN depletion affects the nuclear export of mRNAs and demonstrated that WRN interacts with mRNA and the Nuclear RNA Export Factor 1 (NXF1). Conclusions Our findings suggest that WRN influences the export of mRNAs from the nucleus through its interaction with the NXF1 export receptor thereby affecting cellular proteostasis. In summary, we identified a new partner and a novel function of WRN, which is especially important for the proliferation of cancer cells.